Hubungan Asupan Gizi, Perilaku Makan (Picky Eater) dengan Status Gizi Penderita Austism di Tempat Terapi Autis Kota Pekanbaru - Roziana, Roziana; Humaroh, Yola (Jurnal Kesehatan Komunitas, 2024)
Children with autism are at high risk of experiencing unbalanced nutritional fulfilment, in addition, children with Autism Spectrum Disorders (ASD) tend to have picky eating behavior, behavioral disorders when eating, refusing to eat and being sensitive to the texture and smell of certain foods. Picky eating is one of the eating behaviors that affect nutritional status. Nutritional problems are not only poor nutritional status but short and thin children can also affect the growth and development of children. According to several studies, if picky eating in children is not treated immediately, it will have effects, such as inadequate certain nutrients which will affect nutritional status. Good nutritional status will be achieved if the body gets a balanced intake of nutrients according to needs. To achieve optimal nutritional status and not excessive eating habits autism sufferers must contain the appropriate amount of nutrients to meet physiological needs during growth and development. The eating behavior of autistic children at the autism therapy centre in Pekanbaru City experiences problems with inadequate food intake. Several autistic children always consume only one type of food. This study aims to determine the relationship between nutritional intake, eating behavior (picky eater) and the nutritional status of autism sufferers at autism therapy centres in Pekanbaru City. This cross-sectional study on 90 autistic children was conducted at autism service centres and autism therapy clinics in Pekanbaru City using random sampling techniques. Analysis to determine the relationship between nutritional intake, and eating behavior (picky eater) with nutritional status using the chi-square test with a significance limit of α = 0.05. The results showed a significant relationship between energy, carbohydrate, protein and fat intake and the nutritional status of autistic children (p <0.05). The relationship between iron and zinc intake and the nutritional status of autistic children did not have a significant relationship (p> 0.05). The results of the analysis of the relationship between picky eater behavior and nutritional status showed no significant relationship with a p-value (p> 0.05).